Technology Integration on English Language Learning: A Study of Students’ Engagement at Language Department State Polytechnic of Bengkalis - Fanalisa, Elfa; Paramita, Sari Diah (ABEC Indonesia, 2024)
The aim of this study is to find out the Technology Integration and Student’s engagement on English LanguageLearning at Language Department State Polytechnic of Bengkalis. The Respondents of this research were Seven Lecturersand 30 students of Language Department State Polytechnic of Bengkalis. Observation and questionnaires were used asinstruments to figure out the integration of technology and students’ engagement at Language Department. The findingrevealed that integration of technology on English Language learning showed that the technology was adopted to supportteaching and learning process more effective and efficient. Every course such as Writing, Listening, Speaking, Reading,Grammar and Translation had different approaches in using device and platform. In addition, integration of technologycontributed positive engagement for students in cognitive, affective and behavioral aspects.